HUBUNGAN AGAMA DAN PEKERJAAN SEBAGAI PSK DI KEMBANG KUNING SURABAYA - Bella Ayu D; Nimas Noormala D; Agus Machfud Fauzi; Neny Sujianti Sujianti; Tito Surya Baskara (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
Commercial Sex Work is work that is prohibited by religion but is lawful for those who undergo this work. The woman who works as a commercial sex worker is considered a social disease in the community. In addition to religious factors that are forbidden, economic factors become the cause due to the increasing daily needs. These factors are the cause of someone doing this job. This research uses a descriptive qualitative method using the phenomenology of Alfred Schutz. Data collection techniques in this study using observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this study are that someone who works as a prostitute is not only prohibited by religion but the economic factors that cause him to do this work